2014
DOI: 10.1123/wspaj.2014-0009
|View full text |Cite
|
Sign up to set email alerts
|

Perception vs Reality: Is Perceived or Objective Proximity to Physical Activity Opportunities in the Environment More Associated With Recent Use Among Adolescent Girls?

Abstract: Little is known about adolescent girls’ accuracy of perception of physical activity (PA) opportunities in their neighborhood. Furthermore, few studies have explored whether proximity to PA opportunities is associated with girls’ recent use. Participants included 356 high school girls enrolled in New Moves, a school-based physical activity intervention. Objective proximity to neighborhood PA opportunities was assessed using Geographic Information System (GIS) software. Girls self-reported their perceived proxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Thus, the adolescent who notes the availability of squares/parks near his/her home can achieve higher levels of PA. In this perspective, a research carried out in the United States corroborated the results of the present study, indicating that girls who perceived their home's proximity to a park, walking or running trail or recreational center were associated with the recent utilization of these resources 21 .…”
Section: Discussionsupporting
confidence: 75%
“…Thus, the adolescent who notes the availability of squares/parks near his/her home can achieve higher levels of PA. In this perspective, a research carried out in the United States corroborated the results of the present study, indicating that girls who perceived their home's proximity to a park, walking or running trail or recreational center were associated with the recent utilization of these resources 21 .…”
Section: Discussionsupporting
confidence: 75%
“…They reported that overall activity, measured as time spent in specific geographic locations, was greatest in outdoor settings such as playgrounds and sidewalks, but the authors omitted details on actual use. Perception of greenspace and visiting greenspace were the main foci of another four articles (Barr et al., 2014; Bloesma et al., 2018; Dias et al., 2019; Gallerani et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Moderate to vigorous activity in greenspaces, measured by accelerometers or self‐report, was greater in boys than girls (Mertens et al., 2019; Moore et al., 2014; Van Hecke et al., 2018). Although the type of activity did not necessarily differ for girls, if the proximity of greenspace concerning their place of residence was more than walking distance, they were less likely to use greenspace (Barr‐Anderson et al., 2014; Boone‐Heinonen et al., 2010).…”
Section: Resultsmentioning
confidence: 99%